Impact of Land Uses on Water Availability and Quality in Rural Communities Within the Hohoe Municipality - Marcellinus, A (University of Ghana, 2017)
The Hohoe Municipality in the Volta Region of Ghana has abundant water resources in the form of springs, rivers, streams and groundwater from high yielding aquifers. However, increasing population and economic activities within the municipality have significantly impacted on the availability and quality of these water resources. Rapid urbanization in the municipality includes Likpe, Lolobi, Wli, Fodome, Alavanyo, Santrokofi and Akpafu communities. This study assesses the impact of land use changes on the availability and quality of the main sources of drinking water within the rural areas of the municipality. The impact of land use changes on water resources availability was assessed through Satellite images, administration of questionnaires, interviews and focus group discussions in collaboration with chiefs, opinion leaders, community members and other relevant stakeholders in the municipality. Data for the classification of land use of the study area was derived from analysis of remotely sensed (Landsat 7, Enhanced Thematic Mapper) Satellite image for the year 2007 and (Landsat 8, Enhanced Thematic Mapper) Satellite image for the year 2017 spanning ten years covering the entire Hohoe Municipality from the Centre for Remote Sensing and Geographic Information Systems (CERSGIS), located at the Department of Geography and Resource Development of the University of Ghana for the analysis of land use changes and classification. The data generated by the center showed a detailed land use maps which were classified into the following categories; built up, grassland, forest and bare land for analysis. The result clearly showed an increase in urbanization within the Municipality over the last ten years. Built up has increased from 14.18 % to 21.80 %, grassland coverage has also extended from 26.45 % to 29.95 % while forest areas and bare lands have dwindled drastically from 12.11% to 4.42 % and 5.57 % to 2.14 % respectively . Primary data for the study was derived from field survey carried out in October, November and December 2016. During the field survey sixty (60) questionnaires were administered in the six (6) sub zonal councils of the Hohoe Municipal Assembly namely Likpe, Lolobi , Agumatsa (Wli and Fodome), Alavanyo, Santrokofi and Akpafu communities. Out of the total of sixty respondents interviewed, 65 % were females and 35 % were males within the age range of 40 to 55 years and 56 to 70 years. Majority of respondents (85%) involved in the study asserted that there has been a strong impact of land use changes on water availability and quality within the study area. Water samples were collected from thirty four (34) sampling sites within the various communities namely Alavanyo, Lolobi, Akpafu, Santrokofi, Likpe, Fodome and Wli. In all, twenty one (21) boreholes, three (3) hand dug wells and ten (10) surface water were analyzed to determine the physicochemical quality (pH, EC, temperature, alkalinity, turbidity, colour and TSS), the major ions (Flouride, Chloride, Nitrate, Sulphate, Phosphate, Sodium, Potassium, Calcium and Magnesium) and microbiological quality (fecal coliforms and total coliforms) of the water sources were analyzed. Water samples collected were analyzed by both classical and automated instrumental standard methods for the analysis of water and wastewater (APHA, 2005). Water temperature, Electrical Conductivity (EC), Total Dissolved Solids (TDS), and pH were measured at each sampling site using portable (field-type) instruments (3210 SET 1 conductivity meter and ATC Neuftech - pH meter). The concentrations of ions (Flouride, Chloride, Phosphate, Sulphate, Calcium, Magnesium, Sodium and Potassium) were determined using ion chromatographic techniques (SHIMADZU HIC - 20A model ion chromatograph) and the analysis of microbiological quality was also determined using the membrane filtration method. These were done respectively in Hydrology Laboratory and the Microbiological Laboratory at Ghana Atomic Energy Commission. A Microsoft Excel data analysis tool was used to determine the statistical summary of physicochemical and microbiological parameters. From the study, the physicochemical parameters of surface water and groundwater were within the WHO/ GSA standard of drinking water. The water quality indices (WQI) classified 75 % of groundwater and 70 % of surface water samples as excellent for human use. However, the result of microbiological quality revealed that indicator organisms (total coliform and fecal coliform) were above the WHO/ GSA standards of 0.0 CFU/100ml in all surface water and ground water samples (boreholes and hand dug well) except four (4) boreholes representing 31.7 % that were totally free from fecal coliforms. The chemical characteristics of surface and groundwater show the same cationic dominance of Na+ > K+ > Ca2+ > Mg2+ and anionic dominance Cl- > SO42- > NO3- > PO43-. In conclusion, there is the need to regulate land use activities through enforcement of environmental laws by the Municipal Assembly and agricultural extension officers should organize community based workshops to educate the people on the benefit of best farming practices on their water sources
Keywords: Water Availability; Land Uses; Rural Communities